2003
DOI: 10.1007/bf02988449
|View full text |Cite
|
Sign up to set email alerts
|

Assessment ofTakotsubo (ampulla) cardiomyopathy using99mTc-tetrofosmin myocardial SPECT —Comparison with acute coronary syndrome—

Abstract: Impaired coronary microcirculation might be a causative mechanism of Takotsubo cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 25 publications
5
91
0
7
Order By: Relevance
“…One argument against this includes the observation that left ventricular dysfunction in TTP is not confined to the supply area of one coronary artery. Microvascular spasm is another possible mechanism for inducing myocardial ischemia in TTP (52,64,(70)(71)(72)(73). Investigations of TTP patients with technetium-99m tetrofosmin myocardial single photon emission computed tomography have documented a decreased uptake during the acute phase of TTP, suggesting that impaired coronary microcirculation may play a role in TTP (21,52,64,70).…”
Section: Suggested Pathophysiological Mechanismsmentioning
confidence: 99%
“…One argument against this includes the observation that left ventricular dysfunction in TTP is not confined to the supply area of one coronary artery. Microvascular spasm is another possible mechanism for inducing myocardial ischemia in TTP (52,64,(70)(71)(72)(73). Investigations of TTP patients with technetium-99m tetrofosmin myocardial single photon emission computed tomography have documented a decreased uptake during the acute phase of TTP, suggesting that impaired coronary microcirculation may play a role in TTP (21,52,64,70).…”
Section: Suggested Pathophysiological Mechanismsmentioning
confidence: 99%
“…Kume et al detected the dysfunction of the coronary microcirculation with Doppler flow-wire technique in patients with TS (19). Other authors demonstrated, in patients with TS, abnormalities of the microcirculation through myocardial perfusion scintigraphy with technetium 99 m tetrofosmin (20)(21)(22). A disorder of glucose and fatty acid metabolism, even more, severe of the perfusion defect, has also been demonstrated (23)(24).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Several invasive and non-invasive modalities have been utilized to assess myocardial perfusion both during the acute and recovery phase of TCM. 8,9,[14][15][16][17][18][19][20][21][22][23] These techniques include Doppler guidewire technique, Thrombolysis In Myocardial Infarction (TIMI) frame count (TFC) and TIMI myocardial perfusion grade (TMPG) calculation. 8,9,[14][15][16][17][18][19][20][21][22][23] Gibson et al introduced a novel method in 1996 called 'TIMI frame count' for measuring coronary flow velocity from coronary angiograms.…”
Section: Timi Frame Count a Novel Techniquementioning
confidence: 99%
“…8,9,[14][15][16][17][18][19][20][21][22][23] These techniques include Doppler guidewire technique, Thrombolysis In Myocardial Infarction (TIMI) frame count (TFC) and TIMI myocardial perfusion grade (TMPG) calculation. 8,9,[14][15][16][17][18][19][20][21][22][23] Gibson et al introduced a novel method in 1996 called 'TIMI frame count' for measuring coronary flow velocity from coronary angiograms. [8][9][10] Since then TFC has been used as a quantitative index to determine microcirculatory function in patients with acute coronary syndrome after primary coronary angioplasty as a predictor of functional recovery.…”
Section: Timi Frame Count a Novel Techniquementioning
confidence: 99%
See 1 more Smart Citation